Design and Performance Test of Corn Rice Granulator Machine - ., Warji; Lanya, Budianto; Hardika, Gerry (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2013)
Development in science and technology today has been able to produce instant nutritious foods, such as imitation rice.Â  The application of conventional technologies in the granulation process causes minimal quantity and quality of the imitation rice with corn feedstock generated.Â  The purpose of this research was to design and to test its performance. This research was conducted at the Laboratory of Agricultural Engineering, Agricultural Engineering Department, University of Lampung.Â  This research procedures included several stage: design, assembly, testing, observation and data analysis.Â  The corn rice granulator machine is designed to the specifications of length 140 cm, width 75 cm, and height 170 cm and comes also with other components, such as hopper,Â  sprayer, sweeper, corn rice container, electric motors, gearboxes, pillow block, and couple units.Â  Some of component settings in the testing of this machine: the slope of granulator pan at 35Â°, discharge of hopper 0,2 kg/sec, discharge of water sprayer 0,54 mâ/sec, speed of granulator pan rotation 28 RPM, and the clearance between corn rice container and granulator pan by 5 cm.Â  The results showed that, this granulator machine had production capacity of wet corn rice up to 10,92 kg/hour, and efficiency of granulation up to 78,18%, for the raw material with composition 75% corn flour and 25% tapioca flour. Keywords: Granulator Machine, Imitation Rice, Corn.